Association between the safety climate and occupational injury in the Korean working population: a cross-sectional study - Jeehee Min; Tae-Won Jang; Hye-Eun Lee; Mo-Yeol Kang; Seong-Sik Cho (Epidemiology and Health)
OBJECTIVES Preventing occupational injuries remains a significant challenge in Korea. A positive safety climate can contribute to reducing workplace injuries. However, the impact of safety climate on preventing occupational injuries among the Korean workforce has not been adequately explored. Therefore, this study aimed to investigate the relationship between the perceived safety climate and occupational injuries within the Korean working population. METHODS This study used baseline data from the Korean Work, Sleep, and Health Study (KWSH). The safety climate was measured using the brief version of the Nordic Safety Climate Questionnaire. Occupational injury was determined by whether injuries or accidents had occurred at workplaces in the past year. Logistic regression analysis was performed to examine the association between the safety climate and occupational injury. RESULTS Participants who reported an unfavorable workplace safety climate were more likely to experience occupational injuries. Multiple logistic regression analysis revealed that the adjusted odds ratio (OR) for occupational injuries in an unfavorable safety climate was 2.20 (95% confidence interval [CI], 1.38 to 3.51) compared to a favorable safety climate. Specifically, factors such as “not encouraging employees to follow safety rules when on a tight schedule” (OR, 2.02; 95% CI, 1.25 to 3.24) and “not helping each other work safely” (OR, 1.98; 95% CI, 1.17 to 3.25) were significantly associated with occupational injuries. CONCLUSIONS An unfavorable safety climate was associated with increased occupational injuries among Korean workers. Improving the safety climate in the workplace may reduce occupational injuries in Korea.